Enhancing Public Service Accessibility: The Role and Impact of Single Identity Number (SIN) E-KTP and SIM Integration - Shinwan Fadhil; Hayat Hayat; Andi Tenri Sompa; Suyeno Suyeno (Universitas Padjadjaran, 2023)
The implementation of public services in the Indonesian government often experiences obstacles in transparency, timeliness, and effectiveness in public services. So that technology-based public service innovation is needed to support this progress. The purpose of this paper is to analyze and identify the integration of E-KTP and SIM in realizing SIN to improve public service accessibility. In addition to discussing the integration of the two identities, this paper also explains the benefits received by the community from the development of these technologies. The benefits obtained if the integration of E-KTP and SIM can be realized: efficiency and simplicity, easy access to services, increased mobility, and cost savings. This research was conducted using a qualitative approach with descriptive qualitative methods by collecting data and making comparisons with other countries. Based on the results of the research that has been conducted, it shows that the application of E-KTP and SIM into SIN is very helpful and beneficial for the community because it can increase public trust, efficiency and effectiveness in public services in Indonesia.